Gastric perforation in neonates: Our experience - Fransua Sharafeddin; Brandon Edelbach; Alexandra Vacaru; Georgi Mladenov; Donald Moores; Yogen Singh; Andrei Radulescu (EL-Med-Pub, 2023)
Background: Neonatal gastric perforation (NGP) is a life-threatening condition with a high mortality rate. It accounts for 7% of all gastrointestinal tract (GIT) perforations. The number of NGP cases has been increasing due to the rise in premature and low birth weight neonates. In this study, we present our experience with gastric perforation in neonates. Methods: This retrospective study analyzed all cases of gastric perforation in neonates that were treated at Loma Linda University Medical Center's Neonatal Intensive Care Unit (NICU) between the years 2000 and 2023. The study looked at several variables including patient demographics, birth weight, age at admission and surgery, comorbidities, use of non-steroidal anti-inflammatory drugs (NSAIDs) and steroids, and mortality rate. Results: We treated 15 patients with neonatal gastric perforation (NGP) during the study tenure. The median age at admission was 2 days, with 67% admitted within that timeframe. Surgery occurred at a median age of 5.5 days, and the median birth weight was 2.075 kg, with 26.67% below 1 kg. Males comprised 67%, and 60% had patent ductus arteriosus. Steroids were given to 46.66%, and 30-day mortality was 26.67%, with higher rates among males. Idiopathic cases were common, with notable etiologies including ischemia, necrosis, and congenital anomalies. Primary surgical repair was the main modality, and perforations occurred at various locations. Two cases had necrotizing enterocolitis. Six patients had favorable outcomes, while others experienced mild to moderate complications. Conclusion: Our research supports the idea that males have a worse outcome in terms of both prevalence and survival rates in neonatal gastric perforation (NGP) patients. However, our findings did not confirm the notion that NGP mortality risk is higher in neonates with low birth weight. We also discovered that the median time between admission and surgery in our study group was 1.5 days, emphasizing the importance of early detection of NGP in neonates. Early diagnosis can lead to better decision-making regarding treatment options and surgical intervention.